Biotechnological innovations in food processing. (Biotechnology by Open Learning (Series), 1991)
A thorough examination of the ways in which recent biotechnological developments have led to improvements in food processing. Deals with biotechnology based processes currently in use by or available to the food industry. Building on a series of case studies selected to illustrate the diversity of applications it clearly shows that biotechnology can and will benefit the food industry.